Investigation of catechin’s anti-inflammatory activity: A bioinformatics and molecular docking study - Nisa Yulianti Suprahman; Bulan Rosita Sari; Riri Fauziyya; Fatimah (Acta Biochimica Indonesiana, 2024)
Background: Inflammation plays a key role in the progression of many chronic diseases. As a country with rich biodiversity, Indonesia offers numerous phytochemicals with potential for drug development, including catechin, a natural compound with anti-inflammatory properties. Objective: This study aimed to identify potential anti-inflammatory targets of catechin and evaluate its inhibitory potency through molecular docking simulations. Methods: Data acquisition and refinement were conducted using the NCBI, STRING, and STITCH databases, with intersections identified through Venn diagrams. Molecular docking was performed using AutoDockTools 1.5.6, and interactions were visualized with BIOVIA Discovery Studio. Results: Bioinformatics analysis predicted that catechin inhibits three pro-inflammatory proteins: COX-2, HSP90, and IL-2. Catechin’s inhibitory potential was indicated by negative binding energies and interactions with amino acid residues critical for target protein activity. Among the targets, IL-2 exhibited the lowest binding energy with catechin (-5.12 kcal/mol), suggesting it as the primary anti-inflammatory target. However, catechin’s binding affinity was lower than that of the native ligand (-11.78 kcal/mol). Conclusion: IL-2 is predicted to be the primary target for catechin’s anti-inflammatory activity. Structural modifications of catechin are recommended to enhance its binding affinity and therapeutic potential.